Agile Software Architecture: Perceptions on Quality and Architectural Technical Debt Management - Silveira Neto, Manoel Valerio Da; Malucelli, Andreia; Reinehr, Sheila (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2025: Anais do XIX Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2025)
Software architecture plays a central role in sustaining quality in systems developed using agile methodologies, particularly in large-scale environments. However, the pressure for rapid deliveries and the decentralization of decision-making can compromise attention to quality attributes and exacerbate the accumulation of architectural technical debt. This paper presents the results of an exploratory empirical study involving 14 software architects from a Brazilian financial institution. Using a case study approach with structured interviews, the study investigated professionals’ perceptions regarding the most relevant quality attributes during the architectural design phase and the management of technical debt after the product is released to production. The mixed-methods analysis revealed that functional suitability, security, and reliability are the most prioritized attributes during the design phase, while efficiency and maintainability become more prominent in the post-production phase. Qualitative responses indicated heterogeneous practices, a lack of formalization process for managing technical debt, and weaknesses in the application of architectural tactics. As a contribution, the study offers empirical insights to support future initiatives aimed at systematizing architectural decision-making in agile environments, with attention to quality attributes and organizational factors. This study also adheres to open science principles, making all research materials, anonymized data, and analysis scripts publicly available to foster transparency, reproducibility, and reuse.